Lietuvos TSR istorijos literatūros leidimas 1940–1967 m. (Statistinės medžiagos apžvalga) - Miežinienė, Ala (Knygotyra, 1970)
The development of historical science in Lithuania, the achievements of the Lithuanian Soviet historiography are inseparably linked with the consolidation of Soviet system in Lithuania. The attainments of Soviet historical science in the field of the history of Lithuania are generalized in hisloriographical works by the historians A. Gaigalaite, J. Jurginis and others. In the papers referred to a characteristic of the historiography on the history of Lithuania is given, its problems are pointed out, the main trends of historiography and the principal regularities of the development of Soviet historical science in the field of the history of the Lithuanian S.S.R. are brought out. The aim of this article is to give a survey of the main statistic data on the publication of literature on the history of the Lithuanian S.S.R. in Soviet Lithuania in the period of 1940–1967. In our opinion, these data help in dealing with certain new aspects of the development of Lithuanian Soviet historiography. Together with other historiographical materials, they help to ascertain the main stages of Soviet historical science in the field of the history of Lithuania more exactly. The article adduces statistic data on the history of the Lithuanian S.S.R. published annually in the territory of Soviet Lithuania, the total number of copies and their total volume (the number of pages), etc. On the basis of these materials concluding inferences have been drawn supplementing the picture of the development of Lithuanian Soviet historiography in many respects. The analysis of the statistic data has once again proved great attainments in the historical research on the history of the republic. The data on the publication of historical literature enable us to define concretely the main stages in the historiography on the history of the Lithuanian S.S.R. Even a brief survey of the statistic data shows great opportunities furnished by an analysis of data of this kind. The survey is also indicative of grave problems in the organization and actual state of book statistics. None of the scientific institutions of the Lithuanian S.S.R. disposes of statistic data on the publication of literature on the history of Lithuania. The Book Chamber of the Lithuanian S.S.R in its statistic compendiums does not separate the data on the publication of historical literature on the history of Lithuania from those on the publication of social-political literature at large. Working out exhaustive and comprehensive statistics on the publication of literature in the field of the history of the Lithuanian S.S.R. could be of service not only in solving historiographical problems. It is also important for bibliography, library science, publishing, sociological investigation, etc.